Facial Shape Inheritance Analysis Using Centroid Size : A Geometric Morphometric Study - An'nissa Chusida, - (DR. P. R. YADAV, 2021)
Facial shape assessment, besides being important for forensic identification purposes, is also used in various fields, such as orthodontics, maxillofacial surgery, plastic surgery and clinical genetic. The inheritance of the facial shape is affected by genetic and environmental factors. The method widely used to measure the size and shape of the face is the anthropometric method, but this method is considered inadequate to accurately define the facial shape. The study aims to analyze the inheritance of facial shapes inAustronesian populations using geometric morphometric method. The research was performed in 14 families consisting of 77 subjects with details of 32 subjects of the first generations (G1), 28 subjects of the second generations (G2) and 17 subjects of the third generations (G3). The subjects consisted of 28 men and 49 women aged between 17 and 86 years. The frontal photo was taken and then processed through the tpsUtil, used 25 landmark points that were put through the tpsDig and then geometrically morphometrically analyzed using the morphologika2 v2.5 program.Aonesample binomial test was performed using the log (ln) centroid size value for each family using IBM® SPSS® Statistics Version 26. Results: The results of the one sample binomial test showed no significant differences in the 14 families. In conclusion, no significant differences in the log (ln) value of the centroid size in all families have shown that the facial shape is inherited.